DISTRIBUTIONAL RECORDS OF ORTHOPTERA (INSECTA) FAUNA OF BADALKHOL WILDLIFE SANCTUARY, JASHPUR, CHHATTISIGARH, INDIA - GUPTA, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The paper deals with the study of faunal diversity of Orthoptera of Badakho Wildlife Sanctuary, Jashpur, Chhattisgarh. Altogether 31 species and subspecies pertaining to 29 genera belonging to 6 families of Orthopteran fauna have been reported for the first time from the sanctuary.